Evolution of ternary LixSnyOz artificial cathode-electrolyte interphase (ACEI) through ALD: a surface strengthened NCM811 with enhanced electrochemical performances for Li-ion batteries. (January 2023) - Saha, Arka; Shalev, Ortal; Maiti, Sandipan; Wang, Longlong; Akella, Sri Harsha; Schmerling, Bruria; Targin, Sarah; Tkachev, Maria; Fan, Xiulin; Noked, Malachi
Abstract: [(LiNi0·8 Co0·1 Mn0.1 )O2 ], or NCM811, a member of the Lix Ni1−y−z Coy Mnz O2 (NCM) family of cathode active materials (CAMs), is gaining recognition in the battery community as the CAM of choice for future high energy density lithium-ion batteries, given its high nickel content of c. 80%. Yet, its commercialization is impeded by its mechanochemical instability at a high state of charge (SOC), which results in severe capacity fading and active lithium loss during cycling. In this contribution, we report conformal nanometer-thick (c. 4–7 nm) lithiated tin-oxide ternary coatings (Lix Sny Oz ) deposited on NCM811 cathode powder using the atomic layer deposition (ALD) technique. The first-of-its-kind ALD coating, where Li is being accompanied by a second metal ion (Sn); provides a combination of benefits: (i) it stabilizes the crystal structure, (ii) suppresses electrode polarization, (iii) lowers the voltage hysteresis, and (iv) reduces interfacial and bulk resistance. These improvements all contribute to prolonging the cycling stability of the NCM811 cathode in half-cells (vs. Li/Li + ) at 30 °C and 55 °C and full pouch cells (vs. graphite) at 30 °C. Furthermore, this coating approach is compatible with large-scale production methods and provides a bridge between lab-scale demonstration and industrial manufacturing, thus facilitating the adoption of the developed coating technology by the automobile industry. Graphical abstract: This work focuses on the strategic development of stable Ni-rich NCM811 cathode materials for Li-ion battery application. It involves a simple vapor-phase atomic layer deposition technique to develop novel Li-ion-permeable, lithiated tin-oxide, artificial cathode electrolyte interphase (ACEI). The developed ACEI improves the Li diffusion kinetic of the cell and stabilizes its performances at ambient to elevated temperature. Image 1 Highlights: NCM811 lithium ion cathode Stabilization. Atomic layer deposition of lithiated tin-oxide as artificial cathode electrolyte interphase. Coating improves Li diffusion kinetic and stabilizes its performances.